Uneven Industrial Growth and Regional Disparities: A Comparative Growth Pole Analysis of Krian and Waru Districts - Siti Rosalinda Amaral Pinto; Ike Rizky Olifia; Alivia Novita Nur Laili; Dewi Casmiwati; Sofi Putri Febrianti (Pencerah, 2026)
This study aims to comparatively analyze the industrial development performance of Krian District and Waru District as growth poles in Sidoarjo Regency, East Java, Indonesia. Using a qualitative approach based on a systematic literature review, this study draws on peer-reviewed publications, official statistical reports, and regional planning documents. François Perroux’s Growth Pole Theory serves as the primary analytical lens to examine industrial concentration, spread effects, and spatial disparities between the two districts. The findings reveal that Krian District has developed as a medium-to-large-scale manufacturing center, anchored by the Krian Industrial Zone (KIZ), which supports labor absorption and production capacity. In contrast, Waru District demonstrates more dynamic and diversified economic growth, functioning as a logistics hub, warehousing center, and commercial district, benefiting from proximity to Juanda International Airport and direct access to the Waru–Juanda Toll Road. Infrastructure disparities significantly shape each district’s industrial trajectory, with Waru exhibiting more advanced utility management and transport connectivity. Socially, Waru faces more intense urbanization pressures compared to the relatively stable demographic conditions in Krian. These findings underscore the need for differentiated spatial development policies that leverage each district’s distinct strengths while promoting balanced and equitable regional development within Sidoarjo Regency.